Police Officers’ Opinions about Some Effects of the Use of Body Worn Cameras - Milidragović, Dragan; Milić, Nenad (NBP. Nauka, bezbednosti, policija, 2024)
In the last ten years, many police organizations around the word have been approaching the implementation of cameras that can be placed on the body of a police officer. By implementing these cameras, police organizations strive to prevent and suppress crime, to improve officer safety, officers’ performance and police - community relationship. In September 2023, the Serbian Ministry of Internal Affairs started with the pilot project of implementing body worn cameras (BWC) in two organizational units of the traffic police. The research presented in this paper was carried out before the idea of implementation BWC in Serbian police practice was born. The research included police officers from five organizational units of the Ministry of Internal Affairs. The aim of the research was to explore the views and opinions of police officers related to implementation of BWC. Research results and the authors’ conclusions may help the decision-making process related to the BWC implementation in Serbian police practice.